2008
DOI: 10.1371/journal.pone.0001622
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Evidence in the Archaeal Genomes that tRNAs Emerged Through the Combination of Ancestral Genes as 5′ and 3′ tRNA Halves

Abstract: The discovery of separate 5′ and 3′ halves of transfer RNA (tRNA) molecules—so-called split tRNA—in the archaeal parasite Nanoarchaeum equitans made us wonder whether ancestral tRNA was encoded on 1 or 2 genes. We performed a comprehensive phylogenetic analysis of tRNAs in 45 archaeal species to explore the relationship between the three types of tRNAs (nonintronic, intronic and split). We classified 1953 mature tRNA sequences into 22 clusters. All split tRNAs have shown phylogenetic relationships with other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…There is a great deal of evidence in favour of this view of tRNA origin (Di Giulio, 1992, 1995, 2006a, b, 2008Tanaka and Kikuchi, 2001;Nagaswamy and Fox, 2003;Widmann et al, 2005;Fujishima et al, 2008). One of the strongest pieces of evidence concerns the position of introns in tRNA genes.…”
Section: A Model Of the Origin Of Trna Molecule And The Late Appearanmentioning
confidence: 99%
“…There is a great deal of evidence in favour of this view of tRNA origin (Di Giulio, 1992, 1995, 2006a, b, 2008Tanaka and Kikuchi, 2001;Nagaswamy and Fox, 2003;Widmann et al, 2005;Fujishima et al, 2008). One of the strongest pieces of evidence concerns the position of introns in tRNA genes.…”
Section: A Model Of the Origin Of Trna Molecule And The Late Appearanmentioning
confidence: 99%
“…In our previous research, we found a leader sequence of N. equitans split tRNA Lys and an intron from P. aerophilum tRNA Arg 's possessing similar sequences with 50% identity that were both intervened at an identical nucleotide position, representing a unique example connecting the 2 types of tRNA genes (13). In the current study, a total 3 nucleotide positions were intervened by the leader sequences of C. maquilingensis split tRNAs, such as positions 25/26 and 37/38 in tRNA Gly , 29/30 in tRNA Ala , and 25/26 in tRNA Glu .…”
Section: Evolutionary Relationship Between Split Trna and Intron-contmentioning
confidence: 96%
“…The discovery of these tRNA genes raised the question of whether ancestral tRNA was encoded on a single gene or on separate genes. Our previous study has shown clear phylogenetic relationships among these 3 types of archaeal tRNAs (13). Because N. equitans is a parasite with indications of a massive genome reduction (14), whether its tRNAs represent the ancient form of tRNA or a later product of genome reduction is still unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has indeed been proven that the origin of tRNA genes is polyphyletic (Di Giulio, 2006a). In particular, the existence in Nanoarchaeum equitans of half-genes codifying for the 5′ and 3′ halves of tRNA (Randau et al, 2005), for which there are strong arguments supporting their ancestrality (Di Giulio, 2006a, b;Fujishima et al, 2008), and the assembly of these half-genes to make the complete tRNA molecule (Di Giulio, 1992, 1995, 1999, 2006a pave the way for the logical proof that tRNA genes were assembled in the main phyletic lines and, therefore, their origin was nonmonophyletic (Di Giulio, 2006a, 2008. However, if the origin of genes was polyphyletic, how can it be explained that, as said above, the same proteins from organisms in all three domains of life can form multiple alignments that apparently define these proteins as homologous, thus substantiating their monophyletic origin?…”
Section: Introduction and Hypothesismentioning
confidence: 99%